Spiritualitás a vallásfenomenológia és pasztorálpszichológia horizontján/ 2 - Szabolcs KOVÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2022)
Spirituality at the Horizon of Religious Phenomenology and Pastoral Psychology/ 2. We are living in a designer world, where not only the circumstances but our gods will be created consciously. We hunger for a god. Choosing an inadequate god, a god too small to transcend our limitations and who, therefore, can neither save nor transform us drives us to keep hunting. This study outlines the phenomenology of Christian spirituality, religious practice and highlights their working field. We find correlation between spirituality and spiritual well-being and happiness, factors that contribute to a positive personal development. We are condemned to meaning. There is a universal impulse to endow our joys and sorrows with meaning. Christian spirituality is a condition for us to reframe and understand our life perspectives and reach the “Courage to Be” (Tillich).